2006
DOI: 10.1038/modpathol.3800648
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the receptor for hyaluronic acid mediated motility is an independent adverse prognostic factor in colorectal cancer

Abstract: RHAMM, a member of the microtubule-associated protein family that interacts with the mitogen-activated protein kinase pathway, is associated with tumor progression, aggressive disease and shortened survival in several tumor types. This study aimed to determine the prognostic value of RHAMM in colorectal cancer (CRC). A series of 1420 unselected, nonconsecutive CRC resections were subdivided into three groups: (1) DNA mismatch repair (MMR)-proficient, (2) MLH1 negative and (3) presumed Lynch syndrome. Immunohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 42 publications
(40 reference statements)
1
46
0
Order By: Relevance
“…Furthermore, there is a large body of evidence to show that HA and CD44 are active in many signal pathways (Kobayashi et al 2002, Roscic-Mrkic et al 2003, Bourguignon et al 2005, 2006, Lugli et al 2006, Shi et al 2006. The primer sequence (Kon et al 2006) for CD44 in RT-PCR targeted the transcript for the whole protein.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is a large body of evidence to show that HA and CD44 are active in many signal pathways (Kobayashi et al 2002, Roscic-Mrkic et al 2003, Bourguignon et al 2005, 2006, Lugli et al 2006, Shi et al 2006. The primer sequence (Kon et al 2006) for CD44 in RT-PCR targeted the transcript for the whole protein.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of our previous findings, 11 of these markers were identified as significant and independent prognostic factors in MMR-proficient CRC and, thus, were selected for the current investigation. [10][11][12][13][14][15][16][17] uPA and uPAR also were included in FIGURE 1. Receiver-operating characteristic curves for protein markers that had discriminatory power for survival in lymph node-negative mismatch repairproficient colorectal cancer, namely, urokinase-type plasminogen activator (uPA) (A), uPA receptor (uPAR) (B), p27 (C), and CD8+ tumor infiltrating lymphocytes (D).…”
Section: Discussionmentioning
confidence: 99%
“…Of the protein markers that were chosen for this study, 11 were identified previously that had significant and independent prognostic value in MMR-proficient CRC. [10][11][12][13][14][15][16][17] …”
mentioning
confidence: 99%
“…[18][19][20] Therefore, we recently evaluated the influence RHAMM expression on the survival of acute myeloid leukemia patients using cDNA microarray technology. 21 However, in acute myeloid leukemia, RHAMM expression was associated with a trend towards prolonged survival.…”
Section: Discussionmentioning
confidence: 99%